ENHANCING QUALITY OF EDUCATION: A CASE STUDY ON AN INTERNATIONAL ISLAMIC SCHOOL - Rafikul Islam,; Ibrahim Mohd. Haidoub,; Kazi Md. Tarique, (Asian Academy of Management Journal, 2019)
Private secondary schools that want to gain a competitive edge need to search for effective and creative ways to attract, retain, and foster stronger relationships with students. The decision of selecting a school by the parents for their kids is based on a multitude of factors that differ from one society to another depending on its culture, economic status, religion, and others. The objective of the present research is to identify and prioritise the factors that can enhance the quality of education in an international Islamic school located in Kuala Lumpur from parents’ perspective. The researchers employed both qualitative and quantitative approaches for data collection. The qualitative data were collected through interviewing 10 parents whose kids are currently enrolled in the school, while the quantitative data were collected through a questionnaire survey based on the Analytic Hierarchy Process (AHP). A thematic analysis and AHP were used for analysing the qualitative and quantitative data, respectively. Findings from the thematic analysis resulted in 19 factors; however, only 8 factors with higher frequency were selected to represent the factors expected to enhance the quality of education. The AHP analysis resulted in prioritising these eight factors according to parents’ judgements. The results show that the Islamic environment represents the most desired factor, followed by quality of teachers and school discipline.